The Effect of Parental Participation on Students Motivation to Learn Mathematics Telkom Elementary School Makassar - Sitti Zulaikha Hidayat (Program Studi PGSD FIP UNM, 2021)
This study examines the following problems: (1) How is the description of the participation of parents in Telkom Elementary School Makassar? (2) What is the description of the students' motivation to learn mathematics at Telkom Elementary School Makassar? (3) Is there an effect between parental participation on students' motivation to learn mathematics at Telkom Elementary School Makassar? The objectives of this study are: (1) To determine the description of parental participation in Telkom Elementary School Makassar, (2) To determine the description of students' motivation to learn mathematics at Telkom Elementary School Makassar, (3) To determine whether or not parental participation affects mathematics learning motivation. students at Telkom Elementary School Makassar. The research approach is quantitative research with the type of ex-post facto research. The population in this study were all students of Telkom Elementary School Makassar using the sampling method, namely simple random sampling at each grade level (all students in class 1 Telkom C, 2 Telkom C, 3 Telkom A, 4 Telkom A, 5 Telkom A, and 6 Telkom. B). The sample size is 172 students. The data were collected using a research instrument in the form of a closed questionnaire regarding the participation of parents and students' motivation to learn mathematics which consisted of 35 statements each. Research instruments are validated by experts in their fields. The data analysis technique used was regression analysis with the help of the IBM SPSS Statistic Version 26 application. The results of the descriptive analysis showed that 59 students had parental participation in the high category, 62 students had parental participation in the medium category, and 51 students were in the low category. As well as students who have the motivation to learn mathematics with a high category of 34 students, 123 students in the moderate category, and 15 students in the low category. The results of the regression analysis showed that there was an effect of parental participation of 31.2% on students' motivation to learn mathematics, with a significance value of 0.03. From the research results it can be concluded that there is a positive influence between parental participation on students' motivation to learn mathematics at Telkom Elementary School Makassar in 2020. Keywords: influence, parental participation, motivation to learn mathematics